1982
DOI: 10.1002/em.2860040512
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro genotoxicity of three antihypertensive hydrazine derivatives (hydralazine, dihydralazine, and endralazine)

Abstract: Three antihypertensive hydrazine derivatives (hydralazine, dihydralazine, and endralazine) were found to be genotoxic in four in vivo or in vitro short-term test systems. a) In mice, a single ip administration of the LD50 of the three drugs caused a small but statistically significant increase over controls in DNA elution rate, ie, a modest amount of DNA fragmentation, in three of the four organs (liver, lung, kidney, and spleen) tested, DNA damage being absent in lung for hydralazine and endralazine and in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Sinha and Patterson (1983) found strong binding of hydralazine to DNA and postulated intercalation of the drug between DNA bases. This drug also induced initiation of DNA repair in primary cultures of rat hepatocytes and was mutagenic in the Ames test, further suggesting drug-DNA interaction (Flora et al, 1982). Meltingtemperature measurements showed that hydralazine destabilized double-helical DNA (Eldredge et al, 1974).…”
Section: Introductionmentioning
confidence: 93%
“…Sinha and Patterson (1983) found strong binding of hydralazine to DNA and postulated intercalation of the drug between DNA bases. This drug also induced initiation of DNA repair in primary cultures of rat hepatocytes and was mutagenic in the Ames test, further suggesting drug-DNA interaction (Flora et al, 1982). Meltingtemperature measurements showed that hydralazine destabilized double-helical DNA (Eldredge et al, 1974).…”
Section: Introductionmentioning
confidence: 93%
“…However, the use of hydralazine in the clinic has been implicated in the development of severe forms of systemic lupus erythematosus in patients who have a slow acetylator-phenotype. Furthermore, hydralazine causes DNA damage, and has been reported to induce some incidence of lung tumors in mice [5, 8].…”
Section: Hydralazinementioning
confidence: 99%
“…Isoniazid and iproniazid, monoamine oxidase inhibitors, are in use for the treatment of tuberculosis and, until recently, as an antidepressant, respectively [6, 7]. Hydralazine is a potent arterial vasodilator and plays an important role in the management of hypertension and congestive heart failure [8]. Hydralazine is toxic and induces DNA damage, causes severe forms of systemic lupus erythematosus and has been shown to increase the incidence of lung tumors in mice [5, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…3 Hydralazine is a potent arterial vasodilator and plays an important role in the management of hypertension and congestive heart failure. 4 Hydrazines in general are toxic, and induce a variety of toxic insults. These include liver toxicity, carcinogenicity and mutagenicity.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2, 47 Hydralazine, the least toxic of the hydrazine derivatives, induces DNA damage, 8 causes severe forms of systemic lupus erythematosus, 911 and has been shown to increase the incidence of lung tumors in mice. 46 More recently, hydralazine has been shown to inhibit DNA Methyltransferase 1 by preventing transfer of a methyl group to DNA in several cancer silencing genes/tumor suppressor genes. 9,12 It has, therefore, become an important treatment combination in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%